A Survey of Chemical Compositions and Biological Activities of Yemeni Aromatic Medicinal Plants - Chhetri, Bhuwan K. (Medicines (Basel), 2015)
Yemen is a small country located in the southwestern part of the Arabian Peninsula. Yemen’s coastal lowlands, eastern plateau, and deserts give it a diverse topography, which along with climatic factors make it opulent in flora. Despite the introduction of Western medicinal system during the middle of the twentieth century, herbal medicine still plays an important role in Yemen. In this review, we present a survey of several aromatic plants used in traditional medicine in Yemen, their traditional uses, their volatile chemical compositions, and their biological activities.